Two Decades of Organizational Ethics: A Systematic Review - Maryam Ma'aruf Yakubu; Umar Ibrahim Abbas; Umaru Zubairu (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This paper conducted a systematic review of organizational ethics (OE) articles published over the last two decades, 2000-2020. This paper utilized the Systematic Quantitative Assessment Technique to identify 58 OE articles published by six of the most popular academic publishers in the world: Emerald, Elsevier, Sage, Springer, Taylor and Francis, and Wiley. The review covered five key issues: 1) Time distribution, 2) Geographic distribution, 3) Article type, 4) Data collection methods, and 5) Themes explored. The findings of the systematic review revealed that interest in OE waxed and waned over the two decades covered by this review, and that Africa and South America. The spread between conceptual and empirical OE articles were quite balanced, and survey was the most popular data collection method. Nine themes were identified, with the most striking findings being that having a strong and positive ethical climate had a positive impact on employee and organizational outcomes.